Between Doorkeeper Apartments and Housemaid Rooms: Ways of Living in a Changing Lisbon - Gato, M. A.; Filipa Ramalhete (II Congreso Internacional Cultura y Ciudad La Casa. Espacios domésticos, modos de habitar, 2019)
If the city is a repository of different ways of dwelling that reflect social heterogeneity in terms of class, economic power and social status, the house, as the primary space of intimate and family life, is still the most faithful reflection of these same ways of living and their changes over time. This article proposes to approach processes of social and architectural transformation that marked the domestic space and the culture of living in Lisbon in the mid-20th century. One of the objectives is to illustrate not only how the houses –their architecture, their living– reflect the social, cultural and symbolic values of an era, but also how certain historic characters often underestimated –such as housemaids and doorkeepers– can assume greater prominence in the understanding of the home culture and ways of inhabiting.